NG2‐glia and their functions in the central nervous system. Issue 8 (24th May 2015) - Dimou, L.; Gallo, V.; Götz, Magdalena; Gallo, Vittorio
<x xml:space="preserve">Abstract</x> In the central nervous system, NG2‐glia represent a neural cell population that is distinct from neurons, astrocytes, and oligodendrocytes. While in the past the main role ascribed to these cells was that of progenitors for oligodendrocytes, in the last years it has become more obvious that they have further functions in the brain. Here, we will discuss some of the most current and highly debated issues regarding NG2‐glia: Do these cells represent a heterogeneous population? Can they give rise to different progenies, and does this change under pathological conditions? How do they respond to injury or pathology? What is the role of neurotransmitter signaling between neurons and NG2‐glia? We will first give an overview on the developmental origin of NG2‐glia, and then discuss whether their distinct properties in different brain regions are the result of environmental influences, or due to intrinsic differences. We will then review and discuss their in vitro differentiation potential and in vivo lineage under physiological and pathological conditions, together with their electrophysiological properties in distinct brain regions and at different developmental stages. Finally, we will focus on their potential to be used as therapeutic targets in demyelinating and neurodegenerative diseases. Therefore, this review article will highlight the importance of NG2‐glia not only in the healthy, but also in the diseased brain. GLIA 2015;63:1429–1451